Rewarding mobility? Towards a realistic European policy agenda for academics at risk - Dina Gusejnova; Alina Dragolea; Andrea Pető; Andrei-Vlăduț Terteleac; Artemis Photiadou; Rebeka Bakos (Comparative Migration Studies, 2024)
Abstract This article maps from a critical and comparative perspective how scholars at risk are currently being integrated into the European research infrastructure, as well as in various EU and non-EU Member States. The focus is on three countries ranging from older to newer EU members to one non-EU member state—Hungary, Romania and the United Kingdom—as well as on EU-level organisations. We draw on twelve in-depth interviews conducted with key stakeholders involved in the process of academic migration (non-governmental organisations, EU and national level actors) to identify key issues concerning academics at risk. Finally, we call for a robust EU-level response to an issue that is currently inadequately addressed by national governments, professional associations and NGOs. As we argue, the focus on mobility as a factor supporting research excellence in the regular European research infrastructure can have negative unintended outcomes for scholars at risk. For many of them, rewarding mobility can entail the threat of losing their legal status in temporary places of migration. What is needed is a nuanced approach for scholars at risk in a diverse range of situations, which should involve closer cooperation between international academic bodies and EU policy makers, and complement support for those who need to escape to third countries with the offer of remote work in the country where they are able to obtain a secure residence permit.